2022
DOI: 10.1177/26320843221098427
|View full text |Cite
|
Sign up to set email alerts
|

Randomised evaluation of pre-notification of trial participants before self-report outcome data collection to improve retention: SWAT86

Abstract: Background Retention is considered the second highest trial methods priority in the UK after recruitment. There is limited evidence on whether notifying trial participants that a follow-up questionnaire will be sent soon (‘pre-notification’) affects retention. Methods This Study Within a Trial (SWAT) evaluated whether sending a pre-notification letter or email around 2 weeks before sending a self-report questionnaire increased retention, in terms of provision of the host trial primary outcome. The SWAT was a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The estimated intervention cost per additional participant retained was £53.42, and the total cost per additional participant retained was £46.52. 88 For the text messaging of trial participants, SWAT 35 found that participants randomised to receive a personalised text message were more likely to return their initial postal questionnaire than those who received a standard text message (n = 185/309; 60% vs. n = 160/309; 52%) (RR 1.16; 95% CI 1.00 to 1.33); this represents an absolute percentage difference between intervention groups of 8%. Post hoc subgroup analysis showed that males under 65 years were the group most likely to return their initial questionnaire if they received a personalised text message.…”
Section: Reminders and Promptsmentioning
confidence: 99%
“…The estimated intervention cost per additional participant retained was £53.42, and the total cost per additional participant retained was £46.52. 88 For the text messaging of trial participants, SWAT 35 found that participants randomised to receive a personalised text message were more likely to return their initial postal questionnaire than those who received a standard text message (n = 185/309; 60% vs. n = 160/309; 52%) (RR 1.16; 95% CI 1.00 to 1.33); this represents an absolute percentage difference between intervention groups of 8%. Post hoc subgroup analysis showed that males under 65 years were the group most likely to return their initial questionnaire if they received a personalised text message.…”
Section: Reminders and Promptsmentioning
confidence: 99%
“…The LCTU was responsible for randomisation, monitoring WORKWELL treatment progress, developing and managing online questionnaires and databases, monthly sick leave and all follow-up data collection; missing and minimal data set collection; and all data entry, verification and preparing data for the statistics team. The LCTU also managed the Study Within a Trial (SWAT) evaluating the effect of pre-notification letters on response rates [13]. The trial methodologist (CS) and lead trial statistician (SC) at the University of Manchester worked closely with the team advising on procedures.…”
Section: Original Recruitment Procedures (Fig 1)mentioning
confidence: 99%